Autonomic nervous system correlates of posttraumatic stress symptoms in youth: Meta-analysis and qualitative review. (March 2022) - Siciliano, Rachel E.; Anderson, Allegra S.; Compas, Bruce E.
Abstract: Physiological dysregulation is a key diagnostic criterion for posttraumatic stress disorder (PTSD). While PTSD is defined by trauma exposure, symptom presentations are varied. Similarly, findings of autonomic nervous system (ANS), including parasympathetic (PNS) and sympathetic nervous system (SNS), function in youth exposed to trauma are mixed (e.g., hyporeactivity and hyperreactivity). The present meta-analysis quantitatively assesses the relation between ANS measures broadly, and PNS- and SNS-specific measures, and posttraumatic stress symptoms (PTSS) in youth (ages 4.98 to 19.55 years) across 38 cross-sectional and longitudinal studies ( N = 3488). Findings demonstrate that heightened ANS activity is related to increased PTSS during stress tasks ( r = 0.07), while decreased SNS activity at rest corresponded to increased PTSS ( r = −0.09). The correlation between PNS measures and PTSS was non-significant. The moderation effect of age on the relation between PNS activity measured during stress tasks and PTSS approached significance, such that younger children showed a stronger negative relation between symptoms and PNS activity compared to older youth. Qualitative review of included studies revealed significant variability across sample and stressor characteristics and study methodology. Findings indicate the importance of autonomic dysregulation in youth with PTSS. Additional considerations for future research are discussed. Highlights: Increased ANS reactivity to stress was related to increased PTSS. Decreased SNS activity at rest corresponded to increased PTSS. Potential sources of heterogeneity in findings are discussed. An agenda for future research is outlined. Findings indicate the importance of autonomic dysregulation in PTSD in youth.